(untitled) (Health and Biosciences, 2022)
Self-medication in Brazil is sometimes seen as an immediate solution to stop some symptoms. This action takes place among young people and adults, from 17 to 45 years old, especially those who have greater access to the internet. Access to websites or social networks focused on the health area is, many times, the initial choice for those who cannot afford a medical appointment, have time to consult or have difficulty accessing health services. Drug stores have bet on social networks to keep closer to their consumers. Instagram is a fundamental tool for the sale of medicines. Thus, this study aimed to analyze the information made available on social networks to the population about medicines and compliance with the rules of RDC nº 96/2008. Pages from five drugstores were selected on Instagram and analyzed which subjects are published and whether there are irregularities in these publications related to medicines. Two hundred and sixteen publications were found, in ///which 69 (31.8%) are about cosmetic and hygiene products, 86 (39.8%) are health information and only 05 (2.4%) are specific to medicines. Of the 05 publications on medicines, 03 irregularities were found in 03 publications analyzed, one in each. These drugstores have a lot of influence over their consumers and, to reduce the risk of self-medication, it is very important that the pharmacist acts, both over the counter and on social networks. According to the data found, there are guidelines that encourage healthy habits, but there is also an encouragement to the indiscriminate use of medication on social networks, by drugstores. Thus, the role of the pharmacist is essential, as with the necessary attention, there is clarification of doubts about pharmacotherapy, contribution to the persistence and adherence of treatments, reduction of adverse reactions and toxicities, thus improving society’s quality of life and non-propagation of erroneous information.